A randomized trial comparing live and telemedicine deliveries of an imagery‐based behavioral intervention for breast cancer survivors: reducing symptoms and barriers to care. Issue 8 (22nd August 2014) - Freeman, Lyn W.; White, Rebecca; Ratcliff, Chelsea G.; Sutton, Sue; Stewart, Mary; Palmer, J. Lynn; Link, Judith; Cohen, Lorenzo
Abstract Objective This multi‐site randomized trial evaluates the quality of life (QOL) benefits of an imagery‐based group intervention titled 'Envision the Rhythms of Life'(ERL). Methods Breast cancer survivors >6 weeks post‐treatment were randomized to attend five weekly 4‐h group sessions at a community center with therapist present (live delivery (LD), n = 48), therapist streamed via telemedicine (telemedicine delivery (TD), n = 23), or to a waitlist control (WL) group (n = 47). Weekly individual phone calls to encourage at‐home practice began at session one and continued until the 3‐month follow‐up. Seven self‐report measures of QOL were examined at baseline, 1‐month and 3‐month post‐treatments including health‐related and breast cancer‐specific QOL, fatigue, cognitive function, spirituality, distress, and sleep. Results The Bonferroni method was used to correct for multiple comparisons, and alpha was adjusted to 0.01. Linear multilevel modeling analyses revealed less fatigue, cognitive dysfunction, and sleep disturbance for LD and TD compared with WL across the follow‐up (p's < 0.01). Changes in fatigue, cognitive dysfunction, sleep disturbance, and health‐related and breast cancer‐related QOL were clinically significant. There were no differences between LD and TD. Conclusions Both the live and telemedicine delivered ERL intervention resulted in improvements in multiple QOL domains for breast cancer survivors compared with WL. Further, there were no significant differences between LD and TD, suggesting telemedicine delivered ERL intervention may represent an effective and viable option for cancer survivors in remote areas. Copyright © 2014 John Wiley & Sons, Ltd.